1998
DOI: 10.1016/s0378-1097(98)00361-9
|View full text |Cite
|
Sign up to set email alerts
|

Acetylene reduction and hydrogen photoproduction by wild-type and mutant strains of Anabaena at different CO2 and O2 concentrations

Abstract: Hydrogen photoproduction by growing cultures of Anabaena variabilis and A. azollae did not occur under air+CO P or argon+CO P atmospheres at saturating light but did take place under argon alone. It was shown that CO P inhibited photoproduction of H P as a result of the photosynthetic production of O P whereas photoreduction of C P H P by these cyanobacteria was not inhibited by O P concentrations up to 20% in the assay gas phase. In contrast to the wild type of A. variabilis and of A. azollae, H P photoproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…With the increasing light, the amount of oxygen available for the reaction increases and thus no hydrogen was seen above a certain period of illumination. Tsygankov et al [8] have reported similar results with A. variabilis ATCC 29413 and A. variabilis PK84. The results are strongly supported from the fact that on providing increasing concentration of O 2 in the vials incubated in the dark, hydrogen production decreased.…”
Section: Nitrogenase Activity and Hydrogenase Activitymentioning
confidence: 53%
“…With the increasing light, the amount of oxygen available for the reaction increases and thus no hydrogen was seen above a certain period of illumination. Tsygankov et al [8] have reported similar results with A. variabilis ATCC 29413 and A. variabilis PK84. The results are strongly supported from the fact that on providing increasing concentration of O 2 in the vials incubated in the dark, hydrogen production decreased.…”
Section: Nitrogenase Activity and Hydrogenase Activitymentioning
confidence: 53%
“…In filamentous, heterocystforming diazotrophic strains, this is largely ascribed to the activities of an uptake hydrogenase enzyme system that is functionally closely associated with nitrogenase and oxidizes the H 2 produced 3, [33][34][35] . It has been shown that wild-type Anabaena variabilis cells can generate H 2 only under an argon atmosphere, whereas its uptake hydrogenase mutants PK84 and AVM13 can produce H 2 aerobically 27,[36][37][38] . A recent study also demonstrated H 2 production (~25 µmol per mg of Chl.h) from the vegetative cells of wild-type Anabaena variabilis under nitrogen atmosphere when strict anaerobic conditions are maintained 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The gas phase (214), the age and density of the culture, and the composition, pH, and temperature of the growth medium are also crucial to the final result. Most of the research on cyanobacterial hydrogen production has been carried out with nitrogen-fixing strains (31,55,106,111,166,205,206). In these organisms, the net hydrogen production is the result of hydrogen evolution catalyzed by nitrogenase and of hydrogen consumption catalyzed mainly by an uptake hydrogenase.…”
Section: Cyanobacterial Biohydrogenmentioning
confidence: 99%